Reducing planning target volume margins decreases dose to parotid glands in head and neck cancers - a dosimetric analysis - Kumar, Piyush; Dr. Arvind Kumar Chauhan; Silambarasan, N.S.; Garg, Ayush; Yadav, Rashmi (International Journal of Medical Research and Review, 2019)
Introduction: Radiotherapy in head and neck cancers is treated for several weeks and daily setup and reproducibility is a challenge. This daily variability causes setup errors which accounts planning target volume margins. Reduced PTV margins have to be taken to decrease the dose to the parotid glands, without compromising on loco regional control rates. The present study is done to identify setup errors and see the feasibility to decrease the PTV margins by creating dummy radiotherapy plans in order to decrease dose to parotid glands. Material and Methods: 420 portal images were evaluated for setup errors in three dimensions (Antero Posterior, Left to Right and Superior to Inferior) which were performed in ten patients of oropharyngeal squamous cell carcinoma. All patients were treated in supine position using immobilization cast. After target volume delineation a PTV margin of 7mm was given. Dosimetric parameters of PTV and organs at risk were assessed. PTV margins were calculated according to three methods proposed by Stroom, Van Herk and ICRU 62. Dummy radiotherapy plans were generated using new PTV margins and compared with 7mm PTV margins. The data was analyzed using 3-way ANNOVA test for statistical significance. Results: The optimum PTV margins were 4mm in LR and SI direction and 7mm in AP direction. The PTV parameters (V95, D95, Dmax, Dmean, HI and CI) had no significant difference among different radiotherapy plans with different PTV margins. There was a significant decrease in the dose to right parotid (39.12 Gy to 32.88Gy; p-0.04), left parotid (37.90 to 31.21Gy; p-0.03) and parotid combined (38.65 to 31.45 Gy; p-0.01) when 7mm PTV margins were reduced to 4mm PTV margins. The results of dummy radiotherapy plans using asymmetric PTV margins (LR-4mm, SI-4mm and AP-7mm) and symmetrical PTV margins (4mm in all directions) are compared with PTV margins (7mm in all directions), in terms of PTV and OAR dosimetric parameters. Conclusion: The decreased PTV margins of 4mm decreases the dose to the parotid significantly. The implementation of radiotherapy plans needs to be supplemented by daily IGRT.